UPAYA MENINGKATKAN KEMAMPUAN MENGGUNAKAN APLIKASI GAME QUIZIZ PADA PEMBELAJARAN BLENDED LEARNING - Purwanti, Christina (Persatuan Guru Republik Indonesia Kota Semarang, 2022)
The implementation of this school action research aims to improve the ability of teachers to use the Quiziz application in blended learning through the implementation of teacher mentoring activities. The research subjects were 9 teachers at SD Negeri Rejosari 02. Data collection techniques were observation and documentation techniques. Data analysis was carried out using comparative descriptive techniques. The explanation of increasing teacher ability in using the Quiziz application in blended learning learning in the initial conditions was 45.42 and only entered in the LESS qualification, and in the first cycle the results showed an average score of 69.72 in the C qualification or ENOUGH and at the end of the second cycle increased to 91.67 in the VERY GOOD qualification. In terms of improving the ability of teachers to use the Quiziz application in individual blended learning, it shows an increase, because in the first cycle there were 5 teachers 55.56% who met the success criteria, which were in the GOOD category, in the second cycle all teachers were declared to have increased their skills in using the application. Quiziz on blended learning, because of the 9 teachers there were 6 teachers or 66.67% who met the success criteria, namely in the VERY GOOD category and 3 teachers or 33.33% in the GOOD score criteria. Looking at the data obtained from the research results in this School Action Research activity, it can be concluded that the mentoring carried out by the principal for 9 teachers at SD Negeri Rejosari 02 was declared SUCCESSFUL in increasing the ability of teachers to use the Quiziz application in blended learning